Novel Pharmacological Interventions to Maintain Sinus Rhythm after DC Cardioversion. (12th July 2011) - Thomas, D. E.; Yousef, Z.; Anderson, R. A.
Abstract : Despite the availability of potentially curative interventions for atrial fibrillation, there remains an important role for conventional anti-arrhythmic therapy and anti-coagulation combined with direct current cardioversion. Unfortunately, the latter approach is disturbed by high recurrence rates of atrial fibrillation. In recent years, several adjunctive therapies have emerged which may facilitate the maintenance of sinus rhythm. These novel therapies and their potential mechanisms of action are reviewed in this article.